MICHEL HOUELLEBECQ: FRENCH NOVELIST FOR OUR TIMES. - Karwowski, Michael (Contemporary Review, 2003)
Focuses on the life and works of controversial French writer Michel Houellebecq. Authorship; Emphasis on the philosophy of life of Houellebecq; Views of Houellebecq on the establishment of liberal freedoms.